The factor of war as a threat to sustainable development and a challenge for corporate social responsibility - Korol, Svitlana; Sobchuk, Olena; Bielova, Olena; Shapovalova, Alla (Business: Theory and Practice, 2024)
The purpose of the study is to analyze the practice of involving multinational companies in achieving the Sustainable Development Goals (SDGs), in general, and the response to SDG 16 “Peace, Justice and Strong Institutions”. The research methodology involves a comparative analysis of the attitude towards the SDG leaders of sustainable development and MNCs that currently continue to work on the Russian market is presented. The conducted research showed that MNCs mostly recognize their impact on achieving SDG 16, but at the same time (1) they put it at a medium or low priority level; (2) emphasize justice and strong institutions. As a result of the study, it was proven that the existing approach to assessing the level of achievement of SDG 16 does not take into account modern conditions of warfare and needs to be revised. The novelty of the study lies in the further development of scientific approaches to assessment of international business contribution to SDGs achievement and promotion of sustainable peace, opposition to military aggression, as well as substantiating the need to change approaches (criteria) to assessing the achievement of SDG 16.